Peningkatan Produktivitas Budidaya Ikan Kerapu di Keramba Jaring Apung dengan Pemberian Moist pellet - Henny Fitrinawati; Diana Yulanda Syahailatua; Fadli Jamlean; Dani Ohoiwutun; Royke Betaubun (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
Fish farming activities are the main contributor to the fisheries sector in the coming period by observing the declining trend of marine catches in Maluku. The most widely cultivated fish commodity in Tual City is grouper. PKM partners are grouper cultivators in floating net cages (KJA). During the grouper rearing process, the feed used is trash fish feed from daily catches in nature with the nutritional composition of trash fish being unstable because it depends on the type of fish caught. This is a problem because the availability of feed and feed nutrition is very important for increasing grouper productivity. The stages of the activities carried out, namely socialization, training in making moist pellets, training in handling pests and diseases of fish and monitoring evaluation. From the results of making moist pellets it turns out to be effective enough to be given to groupers. The process of making moist pellets is quite easy by paying attention to the order of weighing the ingredients from the small to the large number of scales. The resulting moist pellets are in a round shape and are adapted to the mouth openings of the groupers that are reared. The behavior of the groupers that were given the moist pellets wanted to eat and was quite responsive because the texture of the moist pellets was soft, the fish had a characteristic odor and was mushy and given until the groupers were full.